EFFECTIVE STRATEGIES FOR INCREASING STUDENT MOTIVATION IN ENGLISH LANGUAGE TEACHING - Rahmatjonov Muhammadiy Bahodirjon o’g’li,; Ashurali Mirzayev Baxtiyor o'g’li, (TADQIQOTLAR, 2026)
Abstract Student motivation is one of the most significant factors influencing success in English  language  learning.  Motivated  students  demonstrate  higher  levels  of engagement, persistence, and academic achievement. This article examines effective strategies for increasing student motivation in English language teaching. It explores the  concept  of  motivation,  the  teacher’s  role,  and  practical  classroom  strategies, including  communicative  activities,  technology  integration,  learner  autonomy, assessment  practices,  and  social  support.  The  findings  suggest  that  motivation  is dynamic  and  can  be  enhanced  through  purposeful  and  student-centered  teaching approaches.